Anthropometry of the facial skeleton in retarded children and youths - Betlejewska, Maria (Anthropological Review, 1980)
Cephalometric examination of 312 retarded persons aged 6-18 years from institutions placed within limits of the Gdańsk voivodeship was conducted. Comparing results of these examinations with data for normal individuals it has been found that in retarded individuals are present abnormalities in growth of all three dimensions of the skull being the strongest in the maxillary part and the weakest un the mandibular one.